Investigation of Peak Ground Acceleration on the Kuala Penyu Fault and Its Influence on the Malaysia National Annex - Harith, Noor Sheena Herayani (International Journal of Sustainable Construction Engineering and Technology, 2025)
This study investigates the peak ground acceleration (PGA) using probabilistic seismic hazard assessment (PSHA) in Kuala Penyu, Sabah. The data from four earthquake events and mud volcano activity in four highly active areas in the region provided the basis for this in-depth study. The PSHA considered parameters such as earthquake data, source modeling, ground motion model (GMM), maximum magnitudes, and logic trees. The evaluations performed in this study were based on three objectives. The first objective is to update the available earthquake catalog around the Sabah region. The second objective is to characterize the seismic source model by determining seismic hazard parameters, including selecting a suitable GMM and identifying the maximum magnitudes. Finally, the third objective is to conduct a PSHA to calculate hazard estimates in terms of PGA. The PGA for Kuala Penyu, Sabah, was measured at 0.106 g, an increase of 430% when considering the Kuala Penyu fault source in the analysis. Based on this significant change, more in-depth studies are needed, particularly in low-seismicity regions with active fault movements, to enhance seismic analysis. This effort could provide better insights into source modeling for seismic hazard assessments in the region.